2013
DOI: 10.1504/ijepee.2013.057908
|View full text |Cite
|
Sign up to set email alerts
|

Economic development as major determinant of Olympic medal wins: predicting performances of Russian and Chinese teams at Sochi Games

Abstract: Abstract:Starting from an econometric model successfully used to explain and then predict the distribution of medal wins across nations at the Beijing Summer Olympics, a similar model is elaborated on with some different explanatory variables for estimating the determinants of medals won per nation at Winter Games. A Tobit estimation of the model based on data from 1964 to 2010 shows that GDP per capita, population, the endowment in ski and winter sports resorts, and a host country dummy are significant determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
3
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 21 publications
0
18
3
4
Order By: Relevance
“…8 The host dummies were not included in the Table 1 regressions because every host included female athletes in their NOC delegation. In addition to the host effect, Johnson and Ali (2004) and Andreff (2013) find broader neighborhood or regional effects; we did not. The coefficients on the first lagged dependent variables, ranging from 0.4 to 0.6, indicate that past outcomes have a nontrivial effect, though perhaps not an overwhelming one.…”
Section: Participation and Performancecontrasting
confidence: 79%
See 2 more Smart Citations
“…8 The host dummies were not included in the Table 1 regressions because every host included female athletes in their NOC delegation. In addition to the host effect, Johnson and Ali (2004) and Andreff (2013) find broader neighborhood or regional effects; we did not. The coefficients on the first lagged dependent variables, ranging from 0.4 to 0.6, indicate that past outcomes have a nontrivial effect, though perhaps not an overwhelming one.…”
Section: Participation and Performancecontrasting
confidence: 79%
“…The host dummies were not included in the Table regressions because every host included female athletes in their NOC delegation. In addition to the host effect, Johnson and Ali () and Andreff () find broader neighborhood or regional effects; we did not.…”
contrasting
confidence: 72%
See 1 more Smart Citation
“…Otamendi and Doncel (2018) raised the issue of whether the medal win distribution is better anticipated by forecasting models or by sports experts who have a deep knowledge of the different Olympic sport disciplines. They compared five expert predictions published in the press with three forecasting models, respectively, used for the 2010 Vancouver Winter Olympics (Otamendi and Doncel, 2014a), the 2012 London Summer Olympics (Otamendi and Doncel, 2014b), and the 2014 Sochi Winter Games (Andreff, 2013). Relying on indicators to test the performance of a forecast such as a ratio of exactly predicted results, Pearson, Kendall, and Spearman correlations adjusting the forecast of ex ante statistical distribution to the ex post observed statistical distribution, the authors concluded that sports experts’ predictions are more accurate as regards the detailed medal distribution within a given sport discipline while econometric models perform better when it comes to medal wins distribution across participating nations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature contains several references on this topic as previously stated. Some refer to the Winter Games (Kuper and Sterken, ; Andreff, ; Otamendi and Doncel, ; Pfau, ), others to the Summer Games (Forrest, Sanz, and Tena, ; Otamendi and Doncel, ), and others to both editions of the Games (Johnson and Ali, ). We adopted a model that predicts the outcome for each sport.…”
Section: Expected Socioeconomic Potential: Sport‐agnostic Econometricmentioning
confidence: 99%